Writing prejudices : the psychoanalysis and pedagogy of discrimination from Shakespeare to Toni Morrison - Samuels, Robert, 1961- (SUNY series in psychoanalysis and culture., 2001)
"Writing Prejudices addresses critical attempts to undermine prejudice through education in general, and literary studies in particular. Robert Samuels argues that these attempts often fail because they do not take into account the different forms of prejudice, the role played by homophobia in racism and sexism, the structure of what Lacan calls symbolic castration, and the unconscious foundations of cultural formations. Addressing these deficiencies, Samuels uses psychoanalytic theory to examine the manifestations of racism, sexism, ethnocentrism, and homophobia in the works of Shakespeare, Mary Shelley, Joseph Conard, and Toni Morrison, showing how these distinct modes of oppression feed off of each other and the diverse ways that cultural critics can work to undermine them."--Jacket